Break free from OCD - Challacombe, Fiona; Oldfield, Victoria Bream; Salkovskis, Paul M. (London Vermillion, 2011)
Are you plagued by obsessive thoughts, rituals or routines? Would you like to regain control over your behaviour and cast your fears aside? Whether you are compelled to wash your hands more and more thoroughly or feel the need to keep checking that you've turned off appliances, obsessive worries can be a drain on daily life. However, you don't need to suffer any more. This practical guide, written by three leading cognitive behavioural therapy experts, enables you to make sense of your symptoms, and gives a simple plan to help you conquer OCD. This title includes: detailed information on the many different manifestations of OCD; the differences between normal and obsessive worries; clear information on treating your individual problem; real-life case studies and examples; and, advice and support for friends and family of OCD sufferers. Whether your condition is mild or severe, this definitive resource will help you reclaim your life and keep OCD away for good.
Keywords: Obsessive-compulsive disorder; Cognitive therapy